Importance of vertical effective stress for reservoir quality in the Skagerrak Formation, Central Graben, North Sea. (December 2016) - Stricker, Stephan; Jones, Stuart J.; Grant, Neil T.
Abstract: The complex fluvial sandstones of the Triassic Skagerrak Formation are the host reservoir for a number of high-pressure, high-temperature (HPHT) fields in the Central Graben, North Sea. All the reservoir sandstones in this study comprise of fine-grained to medium-grained sub-arkosic to arkosic sandstones that have experienced broadly similar burial and diagenetic histories to their present-day maximum burial depths. Despite similar diagenetic histories, the fluvial reservoirs show major variations in reservoir quality and preserved porosity. Reservoir quality varies from excellent with anomalously high porosities of up to 35% at burial depth of >3500 m below seafloor to non-economic with porosities <10% at burial depth of 4300 m below seafloor. This study has combined detailed petrographic analyses, core analysis and pressure history modelling to assess the impact of differing vertical effective stresses (VES) and high pore fluid pressures (up to 80 MPa) on reservoir quality. It has been recognised that fluvial channel sandstones of the Skagerrak Formation in the UK sector have experienced significantly less mechanical compaction than their equivalents in the Norwegian sector. This difference in mechanical compaction has had a significant impact upon reservoir quality, even though the presence of chlorite grain coatings inhibited macroquartz cement overgrowths across all Skagerrak Formation reservoirs. The onset of overpressure started once the overlying Chalk seal was buried deeply enough to form a permeability barrier to fluid escape. It is the cumulative effect of varying amounts of overpressure and its effect on the VES history that is key to determining the reservoir quality of these channelised sandstone units. The results are consistent with a model where vertical effective stress affects both the compaction state and subsequent quartz cementation of the reservoirs.